DESIGN AND IN VITRO CHARACTERIZATION OF FLOATING TABLETS OF METRONIDAZOLE - ESWARAIAH M, CHINNA; S, JAYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to formulate the effervescent floating matrix tablet of metronidazole and to evaluate the effect of varying concentrations of hydrophilic polymers on drug release. Methods: Drug excipients interaction was studied by Fourier transform infrared spectrophotometer. The effervescent floating matrix tablets were prepared by direct compression technique using hydroxypropyl methylcellulose (HPMCK4) and xanthan gum alone and in combination as release retardants. Microcrystalline cellulose was used as diluent. Sodium bicarbonate was used as effervescent agent. The prepared matrix tablets were evaluated for their physicochemical parameters such as weight variation, hardness, friability, content uniformity, buoyancy time, and in vitro dissolution. Results: Micromeritic properties and post-compression parameters were evaluated and all the parameters were found within the acceptable limit. The drug release data were subjected to different models to evaluate release kinetics and mechanism of drug release. The matrix tablets prepared with xanthan gum and a mixture of xanthan gum and HPMCK4 were retarded the drug release up to 12 h. The release mechanism of metronidazole was evaluated on the basis of release exponent n value in Peppas model. The n value of the formulations ranged from 0.46 to 0.89 which indicated Case II transport and zero-order release. Conclusion: Floating matrix tablet is the simple, efficient, and economic method to sustain the release of metronidazole to eradicate Helicobacter pylori in peptic ulcer disease.